Souvenir to Mohammad Ali Jinnah - Jinnah, Mahomed Ali, 1876-1948; Sharif, Rafia (Abdul Hamid Ansari, 1945)
Festschrift honoring Mahomed Ali Jinnah, 1876-1948, on his 70th birth anniversary; comprises of writeups on his life and work.